Impact of aging on food consumption in rural China: Implications for dietary upgrading and health improvement - Gao, Ming; Wu, Bi; Jin, Wencheng; Wei, Jiashuo; Wang, Jiwen; Li, Jinkai (Frontiers in Nutrition, 2022)
Background The issue of population aging in rural China is getting profound; nevertheless, its impact on food consumption has not been well evaluated. This study aims to examine the relationship between rural aging and family food consumption in rural China. Materials and methods Using the statistical yearbook data and the nationally representative household-level data from the China Rural Fixed Observation Points, this study compares the evolution of food consumption between rural and urban residents from 1985 to 2020 and analyzes the structure of food consumption expenditure of rural residents. Next, this study further investigates the impact of aging on food consumption in rural households with ordinary least squares. Results (1) The principal foods consumed by rural residents in 2020 are meat and meat products (36.8%), grain (24.5%), and vegetables (10.9%). (2) An increase in older adults has decreased the absolute consumption of all foods, while it increased relative consumption of meat and meat products, aquatic products, edible oil and fats, poultry, eggs, and sugar. (3) Due to differences in the structure of young adults’ food consumption, older adults would increase their consumption of fruits and vegetables if they lived with younger adults. Conclusion The findings of this study suggest that rural older adults may increase their consumption of fruits and vegetables by advocating intergenerational cohabitation while maintaining their intake of protein to achieve a balanced dietary structure and improve their health condition.